4 - Gender and Research Attainment in Nigerian Agricultural Universities - Oloruntoba, Abayomi; Ajayi, Michael Tunde (Journal of Higher Education in Africa, 2006)
The study uses data on the research outputs of 219 academics in three Nigerian universities of agriculture to compare gender with research attainment. The find- ings show that research attainment is slightly higher for male academics than for female. Academic qualifications and rank are significantly associated with gender and, although there was no significant association between promotion time and gender, male academics have higher publishing rates in journals and proceedings of repute. A high correlation also exists between gender and age, length of service and representation in management. More male faculty members are employed at top management positions, while the majority of female faculty members occupy mid- dle management and entry levels. A policy of gender mainstreaming that would ensure gender balance in recruitment, training and research opportunities could provide a passage through which females gain greater access to positions hitherto dominated by their male counterparts.